Microwave-Assisted Condensation of Two Potential Antibacterial Pharmacophores (Sulfonamide and Oxazolidinone) - Radia Bouasla; Malika Berredjem (Engineering Proceedings, 2024)
In recent years, microwave heating has become a widely used technique in organic synthesis. The reactions take place within a very short time, under mild conditions with high yields, and produce pure and selective compounds with fewer side reactions. In this context and under green chemistry conditions, we synthesized an organic compound containing two pharmacophore groups, oxazolidinone and sulfonamide, with a good yield.